RACIST/PREJUDICIAL PRACTICES IN SPORTS EVENTS (CIPEEX, 2022)
PREJUDICED PRACTICES HAVE BECOME REGULAR IN THE SPORTING CONTEXT, A CONTRIBUTING ELEMENT TO THE SEGREGATION OF GROUPS CLASSIFIED AS SOCIAL MINORITIES AND A DETERMINANT OF VISIBLE PROBLEMS IN THE MIDST OF SOCIAL ISSUES. THEREFORE, THE PROBLEMATIZATION DEFINED FOR THE STUDY IN QUESTION ENCOMPASSES THE FOLLOWING QUESTION: €ŒHOW TO CARRY OUT THE RECOGNITION OF OFFENDERS IN SPORTING EVENTS?€ - ALL THOSE WHO PRACTICE RACIST, HOMOPHOBIC, XENOPHOBIC AND AGGRESSIVE ACTS IN RELATION TO GENDER IN THE CONTEXT OF SPORTS PRACTICES MUST BE UNDERSTOOD AS OFFENDERS. THE MAIN OBJECTIVE OF THE ANALYSIS IN QUESTION IS TO MAKE THE INSPECTION PROCESS POPULAR, SOMETHING INTUITIVE AND EASY TO EXECUTE, IN ORDER TO MAXIMIZE THE REACH OF THE ACTORS AND LEGISLATION RESPONSIBLE FOR THE JUDGMENT AND CONDEMNATION OF INDIVIDUALS WHO COMMIT ACTS OF PREJUDICE IN THESE ENVIRONMENTS. THE DEFINED PROBLEMATIZATION WILL BE SOLVED THROUGH THE CREATION OF AN APPLICATION CAPABLE OF INTEGRATING THE SECURITY AND IDENTIFICATION SYSTEMS PRESENT IN SPACES THAT HOST SPORTING EVENTS, AND ALLOWING ANY SPECTATOR PRESENT TO IDENTIFY AND REPORT THE PERPETRATOR OF THE AGGRESSION BY READING PRE-ORDER CODES. - ESTABLISHED, WHICH WILL BE OF CONSPICUOUS AND MANDATORY USE BY ALL THOSE PRESENT IN THE ENCLOSURE. IN THIS WAY, THE INTEGRATIVE DISCIPLINES INFLUENCED THE DEVELOPMENT OF THE PROJECT THROUGH THE FOLLOWING FRACTIONATION: DATABASE PROJECT (CREATION OF TEXTUAL, ENTITY-RELATIONSHIP AND LOGICAL MODELS FOR THE PROJECT); OBJECT ORIENTED PROGRAMMING (ELABORATION OF CLASSES IN A PROGRAMMING LANGUAGE BASED ON THE OBJECT-ORIENTED PARADIGM (DART), EXPLAINING THE ATTRIBUTES/PROPERTIES, METHODS/PROCEDURES AND INHERITANCES LINKED TO EACH OF THE OBJECTS OF THE REAL PROJECT). THE FORMULATION OF THE PROJECT WILL BE CARRIED OUT ON A CONTINUOUS AND SEMI-ANNUAL BASIS.
Keywords: identification by qr code.; racism in sport; aggression in the sports field